Alcohol consumption, substance use, and depression in relation to HIV Pre-Exposure Prophylaxis (PrEP) nonadherence among gay, bisexual, and other men-who-have-sex-with-men - Paul A. Shuper; Narges Joharchi; Isaac I. Bogoch; Mona Loutfy; Frederic Crouzat; Philippe El-Helou; David C. Knox; Kevin Woodward; Jürgen Rehm (BMC, 2020)
Abstract Background Although HIV pre-exposure prophylaxis (PrEP) substantially diminishes the likelihood of HIV acquisition, poor adherence can decrease the HIV-protective benefits of PrEP. The present investigation sought to identify the extent to which alcohol consumption, substance use, and depression were linked to PrEP nonadherence among gay, bisexual, and other men-who-have-sex-with-men (gbMSM). Methods gbMSM (age ≥ 18, prescribed PrEP for ≥3 months) were recruited from two clinics in Toronto, Canada for an e-survey assessing demographics; PrEP nonadherence (4-day PrEP-focused ACTG assessment); hazardous and harmful alcohol use (AUDIT scores of 8-15 and 16+, respectively); moderate/high risk substance use (NIDA M-ASSIST scores > 4); depression (CESD-10 scores ≥10); and other PrEP-relevant factors. The primary outcome, PrEP nonadherence, entailed missing one or more PrEP doses over the past 4 days. A linear-by-linear test of association assessed whether increasing severity of alcohol use (i.e., based on AUDIT categories) was linked to a greater occurrence of PrEP nonadherence. Univariate logistic regression was employed to determine factors associated with PrEP nonadherence, and factors demonstrating univariate associations at the p < .10 significance level were included in a multivariate logistic regression model. Additive and interactive effects involving key significant factors were assessed through logistic regression to evaluate potential syndemic-focused associations. Results A total of 141 gbMSM (Mean age = 37.9, white = 63.1%) completed the e-survey. Hazardous/harmful drinking (31.9%), moderate/high risk substance use (43.3%), and depression (23.7%) were common; and one in five participants (19.9%) reported PrEP nonadherence. Increasing alcohol use level was significantly associated with a greater likelihood of nonadherence (i.e., 15.6, 25.0, and 44.4% of low-risk, hazardous, and harmful drinkers reported nonadherence, respectively (χ2(1) = 4.79, p = .029)). Multivariate logistic regression demonstrated that harmful alcohol use (AOR = 6.72, 95%CI = 1.49-30.33, p = .013) and moderate/high risk cocaine use (AOR = 3.11, 95%CI = 1.01-9.59, p = .049) independently predicted nonadherence. Furthermore, an additive association emerged, wherein the likelihood of PrEP nonadherence was highest among those who were hazardous/harmful drinkers and moderate/high risk cocaine users (OR = 2.25, 95%CI = 1.19-4.25, p = .013). Depression was not associated with nonadherence. Conclusions Findings highlight the need to integrate alcohol- and substance-focused initiatives into PrEP care for gbMSM. Such initiatives, in turn, may help improve PrEP adherence and reduce the potential for HIV acquisition among this group.